Late onset axonal Charcot-Marie-Tooth phenotype caused by a novel myelin protein zero mutation - Bienfait, H M E; Faber, C G; Baas, F; Gabreëls-Festen, A A W M; Koelman, J H T M; Hoogendijk, J E; Verschuuren, J J; Wokke, J H J; de Visser, M (Journal of neurology, neurosurgery and psychiatry, 2006)
A late onset axonal Charcot-Marie-Tooth phenotype is described, resulting from a novel mutation in the myelin protein zero (MPZ) gene. Comparative computer modelling of the three dimensional structure of the MPZ protein predicts that this mutation does not cause a significant structural change. The primary axonal disease process in these patients points to a function of MPZ in maintenance of the myelinated axons, apart from securing stability of the myelin layer.